2019
DOI: 10.1617/s11527-019-1388-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact behavior of model porous concretes

Abstract: Important note To cite this publication, please use the final published version (if applicable). Please check the document version above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The modulus of elasticity at various saturations was examined. In 2020, authors in [44] reported performing a full stress test on RFC in situ. This experiment was conducted while working on an RFC arch dam in Guizhou Province in southern China.…”
Section: Wwwetasrcom Ihteshaam and Jin: A Comprehensive Literature Re...mentioning
confidence: 99%
“…The modulus of elasticity at various saturations was examined. In 2020, authors in [44] reported performing a full stress test on RFC in situ. This experiment was conducted while working on an RFC arch dam in Guizhou Province in southern China.…”
Section: Wwwetasrcom Ihteshaam and Jin: A Comprehensive Literature Re...mentioning
confidence: 99%